Chapter 11 European Capitals of Culture y Discourses of Europeanness in Valletta, Plovdiv and Galwa - Clopot, Cristina (Taylor & Francis, 2019)
'What is Europe? It's not just a series of banknotes', an interviewee remarked when asked about European heritage. Our study of European Capitals of Culture (ECoC), one of the main European heritage programmes, proceeds in the same spirit, informed by the complex and disputed discussions of what Europe is (see, for example, Sassatelli 2002 ) and how, within such shifting grounds, European heritage might be interpreted (see, for instance, Delanty 2017 ; Niklasson 2017). Described by some as large- scale bottom- up cultural programming (Immler and Sakkers 2014 ), the ECoC programme has seen several cities across Europe compete for the title of European Capital of Culture for more than three decades now. Our research has focussed on three cities, Valletta as ECoC 2018 , Plovdiv as ECoC 2019 and Galway as ECoC 2020. We are conducting a discourse analysis of the submitted bids as the key documents related to each city's participation in the programme; we are then investigating four common themes that emerge from this analysis: Europe, heritage, diversity and future.